Associations between TyG-BMI and normal-high blood pressure values and hypertension: cross-sectional evidence from a non-diabetic population - Peng, Nan; Kuang, Maobin; Peng, Yi; Yu, Hang; Zhang, Shuhua; Xie, Guobo; Sheng, Guotai; Zou, Yang (Frontiers in Cardiovascular Medicine, 2023)
Objective Triglyceride glucose body mass index (TyG-BMI) has been shown to be strongly associated with a variety of chronic diseases. However, little is known about the associations between TyG-BMI and normal-high blood pressure (BP) values and hypertension (HTN). Method The current study was cross-sectional in design and included 15,464 non-diabetic participants recruited between 1994 and 2016 in the NAGALA (NAfld in the Gifu Area, Longitudinal Analysis) study. Associations between TyG-BMI and normal-high BP values and HTN were assessed using multivariate logistic regression. The ability of the TyG index, BMI, and their combined index TyG-BMI to identify normal-high BP values and HTN was compared by receiver operating characteristic (ROC) curves. Results Among the 15,464 eligible non-diabetic participants, 28.56% (4,416/15,464) and 6.23% (964/15,464) had normal-high BP values and HTN, respectively. Multivariate logistic regression analysis showed positive correlations between BMI, TyG index, TyG-BMI and normal-high BP values/HTN; after standardized regression coefficients, TyG-BMI had the strongest association with normal-high BP values and HTN compared to BMI and TyG index. In the fully adjusted model, the odds ratio (OR) value corresponding to the relationship between TyG-BMI and HTN/normal-high BP values was 2.35; when TyG-BMI was used as a categorical variable, compared with the lowest quartile of TyG-BMI the regression coefficient for the association of the highest quartile of TyG-BMI with normal-high BP values increased by 426%, while the regression coefficient for the association with HTN increased by 527%. In further spline regression analysis, we also found that there was a linearly positive correlation between TyG-BMI and systolic BP/diastolic BP (SBP/DBP), which supported the linear trend between TyG-BMI and HTN/normal-high BP values (P-trend <0.0001). In addition, ROC analysis showed that TyG-BMI had good diagnostic values for both normal-high BP values and HTN, and TyG index combined with BMI can significantly improve the ability of a single index to identify normal-high BP values and HTN. Conclusion In the non-diabetic population, TyG-BMI showed a significant positive correlation with both normal-high BP values and HTN, and TyG-BMI was of higher value for the identification of both normal-high BP values and HTN compared to BMI and TyG index alone.